Provision of Fermented Coffee Skins as Additional Feed For The Growth of Goats - I Dewa Nyoman Sudita; I Gusti Agus Maha Putra Sanjaya; Ni Made Ayu Gemuh Rasa Astiti. (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Coffee skin is one of the wastes generated from coffee bean processing which is still potentially used as animal feed through the fermentation process, especially for goats as ruminants. Coffee skin fermentation using local micro-organisms (LMO) produces the best quality, and the provision of 10% substitution has a significant effect on the growth of pigs. The purpose of this study was to be able to determine the response to the appearance of prospective parent goats given fermented coffee husk waste as additional feed to their growth before the reproductive phase. The method used in achieving these objectives is the experimental design method using a Completely Randomized Design (CRD) with 4 treatments, namely: without additional coffee husk (Ko), giving coffee skin 5% (K1), 10% (K2), and 15% (K3) and each treatment was repeated 3 times. The basic feed given is in the form of forage mixed with grass and legumes, and coffee skin is given before being given forage. The results showed that giving fermented coffee skins additional feed had a significant effect (P<0.05) on body weight gain. The higher the level of fermented coffee peels the higher the average added weight until the level of 15% (K3) showed the best results with an additional body weight of 211g/day, but not significantly different (P> 0.05) with K1, and K2. From this study, it can be concluded that the provision of fermented coffee skin waste as additional feed has a significant effect on the additional body weight of goats up to a level of 15%.